An Untested and Uncooperative Pediatric Patient Undergoing a Dental Procedure Using a Negative Airflow Tent During the Coronavirus Disease 2019 Pandemic: A Case Report. Issue 2 (February 2021) - Deng, Taylor A.; Tsui, Ban C. H.
Abstract : The coronavirus disease 2019 (COVID-19) pandemic prompted the creation of novel techniques to protect patients and health care providers. Simulations showed that disposable oxygen face tents act as a physical barrier and can be repurposed as a negative airflow tent. This case study presents a pediatric patient requiring dental surgery, ineligible for preoperative testing for COVID-19 due to developmental delay and aggression. Precautionary measures were taken by means of full personal protective equipment (PPE) and negative airflow tent. The tent added additional protection and is a promising new technique that is disposable, widely available, and offers full access to proceduralists.